The Analysis of Students’ Critical Thinking Skill in Blended Learning - Ni Putu Artila Dewi; Ni Made Dita Sintadewi; Made Detri Suryantini (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
In learning English, blended-learning is the newest approach in this technology era. Blended-learning supports traditional and online discussion in teaching learning process. Blended-learning leads of students’ critical thinking in learning process. This article focuses in descriptive qualitatif approach. Data collection is from observation, interview and questionnaire. The aims of this article is to analyze students’ critical thinking process that is found during blended-learning process in fourth semester English Language Education of Universitas Triatma Mulya academic year 2023-2024. Observation is conducted to see the students’ critical thinking process during the students on online class. The result of this study is blended-learning approach especially online discussion can improve the students’ critical thinking process. It means that teaching English through blended-learning effective for increasing the students’ critical thinking.